PENGARUH PERSEPSI DUKUNGAN ORAGANISASI TERHADAP KINERJA KARYAWAN DENGAN KETERLIBATAN KARYAWAN SEBAGAI VARIABEL MEDIASI (STUDI DI UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA) - Rismanto Rismanto (JURNAL EKOBIS DEWANTARA, 2020)
The purpose of this study was to determine the effect of perceived organizational support on employee performance with employee engagement as a mediating variable. The data used in this study are primary data resulting from the distribution of questionnaires to 50 respondents. The respondents in this study were employees of Sarjanawiyata Tamansiswa University Yogyakarta. The analysis technique used is simple linear regression analysis with the help of SPSS version 16.00 for windows. The results of this study indicate that: 1) Perception of organizational support influences employee involvement, 2) Perception of organizational support influences employee performance, 3) Employee involvement influences employee performance, 4) Employee involvement is proven to mediate the effect of perceived organizational support on employee performance.